2014
DOI: 10.1136/annrheumdis-2013-204762
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tocilizumab on osteitis, synovitis and erosion progression in rheumatoid arthritis: results from the ACT-RAY MRI substudy

Abstract: ObjectiveTo examine the imaging-detected mechanism of reduction of structural joint damage progression by tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) using MRI.MethodsIn a substudy of a randomised, double-blind, phase 3b study (ACT-RAY) of biologic-naïve patients with RA who were methotrexate (MTX)-inadequate responders, 63 patients were randomised to continue MTX or receive placebo (PBO), both in combination with TCZ 8 mg/kg every 4 weeks, with optional additional disease-modifying antirheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
(29 reference statements)
3
42
1
1
Order By: Relevance
“…The same results were found in the study of P. G Conaghan et al [7] in patients with RA treated with Golimumab plus MTX significantly improved MRIdetected synovitis and osteitis at weeks 12 and 24, and in the study of Suzuki et al [6] in patients with RA treated with tocilizumab at 44 weeks but not at 20 weeks. Recently, Conaghan PG et al [38] had found a rapid suppression of synovitis and osteitis with reduction in structural joint damage progression occurred with TCZ, as monotherapy or in combination with MTX, through week 52. However, in 2 others studies, there was an improvement of the RAMRIS erosions score, while the modification of RAMRIS synovitis and RAMRIS oedema scores remain trivial.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were found in the study of P. G Conaghan et al [7] in patients with RA treated with Golimumab plus MTX significantly improved MRIdetected synovitis and osteitis at weeks 12 and 24, and in the study of Suzuki et al [6] in patients with RA treated with tocilizumab at 44 weeks but not at 20 weeks. Recently, Conaghan PG et al [38] had found a rapid suppression of synovitis and osteitis with reduction in structural joint damage progression occurred with TCZ, as monotherapy or in combination with MTX, through week 52. However, in 2 others studies, there was an improvement of the RAMRIS erosions score, while the modification of RAMRIS synovitis and RAMRIS oedema scores remain trivial.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with TCZ also inhibited progression of radiographic joint damage as measured by X-ray within 6 months of treatment initiation. However, there are limited data on the tissue-level effects of TCZ [2].…”
Section: Introductionmentioning
confidence: 97%
“…The efficacy and safety of TCZ monotherapy and TCZ in combination with disease-modifying anti-rheumatic drugs were shown in adult patients with RA in five pivotal phase 3 clinical trials [2]. Treatment of patients with TCZ also inhibited progression of radiographic joint damage as measured by X-ray within 6 months of treatment initiation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations